GENERALIZED HYERS-ULAM -RASSISA STABILITY OF AN ADDITIVE β1, β2 -FUNCTIONAL INEQUALITIES WITH THREE VARIABLES IN COMPLEX BANACH SPACE - VAN AN, LY (IJRDO -JOURNAL OF MATHEMATICS, 2022)
In this paper we study to solve the of additive β1, β2 -functional inequality with three variables and their Hyers-Ulam stability. First are investigated in complex Banach spaces with a fixed point method and last are investigated in complex Banach spaces with a direct method. I will show that the solutions of the additive β1, β2 - functional inequality are additive mapping. T hen Hyers Ulam stability of these equation are given and proven. T hese are the main results of this paper.